Social Media for Collaborative Student Sustainability - Mataac, Chito (NIDA Development Journal, 2025)
This study examines how students utilize social media to collaborate on sustainable consumption initiatives on campus. The objectives include analyzing the effectiveness of social media functionalities in supporting sustainability efforts, identifying student-driven sustainable practices, and proposing platform improvements to enhance collaboration. A survey questionnaire was administered to 460 undergraduate students using convenience sampling, with responses collected in both Thai and English. The study employed a mixed-methods approach, utilizing descriptive statistics and frequency analysis for quantitative data, while thematic analysis was conducted on open-ended responses to identify key trends in student collaboration. The results present that over 80% of students actively engage with social media platforms, primarily Line (80%), Facebook (77.8%), and Instagram (72.0%), using them for communication, organizing sustainability projects, and mobilizing participation. Key themes from the analysis draw attention to the role of social media in enhancing outreach, real-time engagement, and knowledge sharing. However, students identified challenges, such as the lack of integrated collaboration tools, limited content discovery features, and insufficient analytics to measure engagement. The study recommends improving social media platforms by incorporating project management tools, refining content discovery algorithms, and integrating sustainability-focused educational resources. These findings provide insights for universities, social media developers, and policymakers to strengthen digital sustainability strategies and promote student-led environmental initiatives on campus.